Nocturnal Oviposition Behavior of Necrophagous Dipterans in Kelantan, Malaysia - Hadi, Helmi; Jayaprakash, Paul T. (Wiley, 2009)
The likelihood of dipteran maggots colonizing a corpse due to nocturnal oviposition can be used to challenge the postmortem interval (PMI) estimated assuming diurnal oviposition. Earlier experiments tested nocturnal oviposition behavior by exposing fresh baits once during a single night. In this pilot study, oviposition behavior was studied using beef baits, which, simulating the decay of the body seen in case situations, decomposed inside cages designed to open and close at scheduled intervals during consecutive night or twilight periods. Freshly hatched maggots from diurnally oviposited eggs emerged in control baits on the third day, while a limited number of maggots attributable to nocturnal or twilight oviposition were observed in experimental baits only on the fifth or sixth day, indicating a categorical delay. These results suggest that such delayed and limited nocturnal oviposition is not forensically significant since the larger maggots deriving from diurnal oviposition would be the ones considered when estimating PMI.